A systematic review of paediatric neurogenic lower urinary tract dysfunction guidelines using the Appraisal of Guidelines and Research Evaluation (AGREE) II instrument. (19th October 2022) - Yadav, Priyank; Alsabban, Abdulrahman; de Los Reyes, Thomas; Varghese, Abby; Ming, Jessica M.; Milford, Karen; Yang, Stephen S.; Silangcruz, Jan M.; Dos Santos, Joana; Bagli, Darius J.; Rickard, Mandy; Lorenzo, Armando J.; et al.
Abstract : Objective: To examine and critique current international clinical practice guidelines (CPGs) on management of paediatric neurogenic lower urinary tract dysfunction (NLUTD) and assess the applicability of these guidelines to clinical practice. Materials and Methods: We conducted a systematic review of all CPGs on NLUTD published in English from the year 2010 to 2022. Six reviewers independently used the Appraisal of Guidelines and Research Evaluation (AGREE) II instrument to appraise all eligible CPGs. This instrument is comprised of 23 items organised into six quality domains. The scores for each item and domain were tabulated for each reviewer and interrater reliability was assessed for each domain using the intraclass correlation coefficient (ICC). Results: Six CPGs were appraised and these included: National Institute for Health and Care Excellence (NICE), European Society for Paediatric Urology, International Children's Continence Society, Irish, Spina Bifida Association (SBA), and International Brazilian Journal of Urology guidelines. They had high mean standardised scores in the domain on 'scope and purpose' and 'clarity of presentation' but had low scores in the domain of 'applicability'. The top three CPGs based on overall score were the NICE, Irish and SBA guidelines and the reviewers had high degree of interrater reliability (ICC 0.912, P < 0.001). The mean scores in various domains for the top three guidelines were 95.8 (scope and purpose), 87.5 (stakeholder involvement), 69.1 (rigour of development), 94.0 (clarity of presentation), 68.4 (applicability), and 59.7 (editorial independence). The diagnostic and treatment recommendations of the top three guidelines were presented. Conclusion: The existing CPGs on paediatric NLUTD provide high‐quality evidence based recommendations. The NICE, Irish and SBA guidelines were the top three CPGs identified. They scored high on most domains except applicability and editorial independence. These domains need to be considered for future updates to improve the utility.